The effectiveness of two silicone dressings for sacral and heel pressure ulcer prevention compared with no dressings in high‐risk intensive care unit patients: a randomized controlled parallel‐group trial. (1st August 2020) - Hahnel, E.; El Genedy, M.; Tomova‐Simitchieva, T.; Hauß, A.; Stroux, A.; Lechner, A.; Richter, C.; Akdeniz, M.; Blume‐Peytavi, U.; Löber, N.; Kottner, J.
Summary: Background: There is a high incidence of pressure ulcers in high‐risk settings such as intensive care. There is emerging evidence that the application of dressings to pressure ulcer predilection areas (sacrum and heels) improves prevention strategies. Objectives: To determine whether preventive dressings, applied to the sacrum and heels of high‐risk patients in intensive care units, in addition to standard prevention, reduces the incidence of pressure ulcers. Methods: Between June 2015 and July 2018, a randomized, controlled, two‐arm, superiority pragmatic study was performed with a concealed 1 : 1 allocation to the intervention and control group. Patients assigned to the intervention group had dressings applied to the sacrum and heels. Results: In total, 7575 patients were screened for eligibility and 475 patients were included and allocated to both groups. Finally, 212 patients in the intervention group and 210 in the control group were analysed. The mean age was 63·5 years and the majority of patients were male (65·4%). The cumulative pressure ulcer incidence category II and above was 2·8% in the intervention, and 10·5% in the control group ( P = 0·001). Compared with the control group, the relative risk in the intervention group was 0·26 [95% confidence interval (CI) 0·11–0·62] and the absolute risk reduction was 0·08 (95% CI 0·03–0·13). Conclusions: The results indicate that the application of dressings, in addition to standard prevention, in high‐risk intensive care unit patients is effective in preventing pressure ulcers at the heels and sacrum. What's already known about this topic? Pressure ulcers are severe soft tissue injuries and wounds, which occur worldwide in all healthcare settings. Despite preventive interventions, pressure ulcers still develop. There is emerging evidence that dressings help to prevent pressure ulcers. What does this study add? The incidence of pressure ulcers in intensive care units among high‐risk patients remains high. The application of dressings to the sacrum and heels, in addition to standard preventive measures, reduces the relative and absolute risks for the development of pressure ulcers. The application of preventive dressings at the heels and sacrum seems to be feasible in intensive care settings. Linked Comment: Nixon. Br J Dermatol 2020; 183:200–201 .